Can lab experiments help design personnel policies? - Marie Claire Villeval (IZA World of Labor, 2016)
Can a company attract a different type of employee by changing its compensation scheme? Is it sufficient to pay more to increase employees' motivation? Should a firm provide evaluation feedback to employees based on their absolute or their relative performance? Laboratory experiments can help address these questions by identifying the causal impact of variations in personnel policy on employees' productivity and mobility. Although they are collected in an artificial environment, the qualitative external validity of findings from the lab is now well recognized.
Keywords: C9; J3; J6; J7; M5; 330; laboratory experiments; behavior; incentives; evaluation; peer effects; human resource management